(untitled) (Analysis in Theory and Applications, 2017)
In the present paper, a new difference matrix via difference operator D is introduced. Let x = (x_k) be a sequence of real numbers, then the difference operator D is defined by D(x)_n = ∑^n_k=0 (−1)^k(matrixn n−k matrix)x_k, where n = 0,1,2,3,···. Several interesting properties of the new operator D are discussed.